(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the artistic and educational significance of fantasy and mythological elements in children’s literature with particular emphasis on the literary works of J. R. R. Tolkien. Fantasy literature contributes to children’s imagination, emotional development, and moral education through symbolic narratives, magical worlds, and mythological motifs. The study analyzes the functions of fantasy literature, the role of mythological symbolism, and the cultural influence of Tolkien’s fictional universe. Drawing from literary criticism, mythology studies, and children’s literature theory, the article explores how fantasy narratives shape children’s intellectual and emotional perception.